Socialization of BOTAFA: Fauna Hand Puppets as Educational Media for Indonesian Fauna at SDN 22 Kuranji - Rafia Rafia; Fajar Irianto; Alivia Zulkarnain; Feskaharny Alamsjah (Warta Pengabdian Andalas, 2024)
Human activities pose significant threats to the biodiversity of Indonesia, leading to a decline in the population of endemic animals. Insufficient awareness among the public regarding the importance of conservation exacerbates wildlife trafficking and decreases animal populations. To enhance awareness, early-age education is crucial. Hand puppets, as educational tools, offer an engaging and practical approach to teaching children about Indonesian fauna. The implementation of Fauna Hand Puppetry (FHP) was conducted at SDN 22 Kuranji, and through a series of hand puppets, illustrated storybooks, and QR-coded tags linked to a website, the socialization aimed to capture children's interest and provide easy understanding of the protected fauna. FHP products are designed with child-safe materials and attractively packaged, empowering children to take an active role in conservation. Socialization methods involve PowerPoint (PPT) presentations to explain Indonesian wildlife and interactive Q&A sessions to allow students to inquire and discuss the presented materials. Through a combination of presentations and Q&A sessions, this socialization effort is anticipated to foster a better understanding among students regarding the importance of protecting Indonesian fauna. The quiz and Q&A session results conducted after the socialization showed that students' understanding increased, and they could answer an average of 9 out of 10 questions correctly related to Indonesian fauna.